Non-synergistic cytotoxic effects of Fusarium and Alternaria toxin combinations in Caco-2 cells. (22nd January 2016) - Vejdovszky, Katharina; Warth, Benedikt; Sulyok, Michael; Marko, Doris
Highlights: Antagonistic effects of combined Fusarium mycotoxins at high concentrations. Tenuazonic acid seems to decrease the cytotoxicity of deoxynivalenol. Enniatin B showed stronger cytotoxicity in Caco-2 than deoxynivalenol or nivalenol. Aurofusarin mediated pronounced cytotoxicity—first toxicological characterization. Aurofusarin lead to additive effects on cytotoxicity with other mycotoxins. Abstract: Exposure of humans and animals to mycotoxins via food and feed generally involves a conglomeration of compounds contaminating the consumed products. Investigations on combinatory effects of mycotoxins are therefore of great importance. In this study, cytotoxic effects of binary mixtures of the Fusarium toxins enniatin B, aurofusarin, deoxynivalenol, nivalenol and zearalenone, and tenuazonic acid produced by Alternaria spp ., were evaluated by the WST-1 assay in the colorectal carcinoma cell-line Caco-2 after 24 h of incubation. The selection of these mycotoxins was based on typically occurring natural contamination patterns in grains. Aurofusarin, which can be found abundantly in contaminated foodstuff and has not been toxicologically characterized properly so far, showed pronounced cytotoxicity, decreasing the mitochondrial activity at 10 μM to 51% compared to a solvent control. Combinations of other mycotoxins with aurofusarin showed additive effects. In contrast, binary mixtures of enniatin B, deoxynivalenol, nivalenol and zearalenone at cytotoxic concentrations, predominantly resulted in antagonistic effects. Binary combinations of these four Fusarium toxins with tenuazonic acid also revealed interacting effects leading to a decrease in cytotoxicity, compared to expected combinatory effects. Especially in combination with deoxynivalenol, tenuazonic acid was found to significantly reduce the cytotoxicity of this mycotoxin in Caco-2 cells. Synergistic effects were not observed for any toxin combination under the chosen conditions.